HARMONIZATION OF FINISHED GOODS ACCOUNTING IN MANUFACTURING ENTERPRISES WITH INTERNATIONAL ACCOUNTING STANDARDS - Pashakhodjayeva, Dildora; Niyazova, Firuza (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
The article analyzes the harmonization of finished goods accounting in manufacturing enterprises with international accounting standards. It highlights differences between national and international approaches and proposes methods for alignment. The results emphasize the importance of harmonized accounting for financial transparency. The study also examines the practical challenges faced by manufacturing enterprises during the implementation of international accounting standards, including issues related to valuation, recognition, and disclosure of finished goods. Special attention is given to the role of regulatory frameworks and institutional support in ensuring effective harmonization processes. Furthermore, the article explores the impact of harmonized accounting practices on managerial decision-making, investment attractiveness, and overall financial reporting quality. It is noted that aligning national accounting systems with international standards contributes to increased comparability of financial statements and facilitates integration into the global economic environment. The paper concludes that the harmonization of finished goods accounting is a crucial step toward improving the efficiency and transparency of accounting systems in manufacturing enterprises, and provides recommendations for further development and implementation of unified accounting approaches.